Proceedings of the 2nd International Conference on Sports Sciences and Health 2018 (2nd ICSSH 2018) 2019
DOI: 10.2991/icssh-18.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Body Mass Index (BMI) With Agility of Elementary School Children

Abstract: The purpose of this study was to determine the relationship between BMI of male and female students with agility level. This study uses a cross-sectional method; the subject of the study is students of elementary school level second to sixth grade. The conclusion of this study is that there is no significant difference in BMI between boys and girls. Agility in boys is better than agility in girls and there is no significant relationship between BMI and the level of agility in elementary school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
2
0
3
Order By: Relevance
“…The interpretation can be that male preschoolers did not differ by their physique from female preschoolers. This result can be supported by studies that reported that the BMI of elementary school students does not vary according to gender [48,49].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The interpretation can be that male preschoolers did not differ by their physique from female preschoolers. This result can be supported by studies that reported that the BMI of elementary school students does not vary according to gender [48,49].…”
Section: Discussionsupporting
confidence: 57%
“…Cale and Harries emphasized the importance of physical activities-the process indicators-over consequent indicators, such as physical fitness or abilities [60]. As emotional satisfaction and happiness from being able to move the body freely as physical abilities, such as muscular endurance, muscular strength, flexibility, and balance, develop during babyhood have a positive effect on the formation of ego [48], it is necessary to establish and run exercise programs that involve various physical fitness factors. Hence, a multidirectional approach toward children's physical fitness analysis is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Latihan tersebut yang kurang difokuskan oleh pelatih pada saat latihan yang dilakukan oleh reaponden. Usia merupakan faktor penting dalam agility semakin mendekati usia dewasa maka kekuatan otot juga akan bertambah sehingga agililty yang dihasilkan juga akan lebih baik [12].…”
Section: Pendahuluanunclassified
“…Faktor intrinsik dan faktor ektrinsik itulah yang seharusnya didapat oleh responden pada saat pengambilan data untuk mengasilkan performa pada saat tes agility maksimal, namun hal tersebut tidak dapat dikendalikan oleh peneliti. [12]. Terdapat beberapa hal yang menyebabkan hasil pada penelitian ini tidak terbukti, yaitu latihan yang kurang berfokus terhadap peningkatan agility para pemain klub futsal Sahabat Junior Pangkalan Lesung yang memiliki pengaruh besar terhadap peningkatan agility pemain, yaitu dalam meningkatkan kekuatan otot dan fungsi koordinasi.…”
Section: Pendahuluanunclassified
“…Perhatian secara mendalam terhadap aktifitas anak perlu dilakukan mengingat bahwa perbedaan gender dapat mempengaruhi tingkat perbedaan kapasitas fisikal. Berdasar pada usia sekolah dasar tingkat kapasistas fisikal e.g; kelincahan, kecepatan, koordinasi keseimbangan serta indeks masa tubuh memiliki tingkat perbedaan dimana tidak selalu anak laki-laki yang memiliki tingkat kapasitas lebih tinggi (Hariadi et al, 2019;Iri et al, 2017). Pemantauan secara berkala terhadap anak menggunakan instrumen yang disarankan sangat efektif untuk meningkatkan tingkat kesegaran jasmani (Kolle et al, 2020;Leuciuc, 2017).…”
Section: Hasilunclassified